New Horizons of Macrophage Immunomodulation in the Healing of Diabetic Foot Ulcers - Ching-Wen Lin; Chien-Min Hung; Wan-Jiun Chen; Jui-Ching Chen; Wen-Yen Huang; Chia-Sing Lu; Ming-Liang Kuo; Shyi-Gen Chen (MDPI AG, 2022)
Diabetic foot ulcers (DFUs) are one of the most costly and troublesome complications of diabetes mellitus. The wound chronicity of DFUs remains the main challenge in the current and future treatment of this condition. Persistent inflammation results in chronic wounds characterized by dysregulation of immune cells, such as M1 macrophages, and impairs the polarization of M2 macrophages and the subsequent healing process of DFUs. The interactive regulation of M1 and M2 macrophages during DFU healing is critical and seems manageable. This review details how cytokines and signalling pathways are co-ordinately regulated to control the functions of M1 and M2 macrophages in normal wound repair. DFUs are defective in the M1-to-M2 transition, which halts the whole wound-healing machinery. Many pre-clinical and clinical innovative approaches, including the application of topical insulin, CCL chemokines, micro RNAs, stem cells, stem-cell-derived exosomes, skin substitutes, antioxidants, and the most recent Phase III-approved ON101 topical cream, have been shown to modulate the activity of M1 and M2 macrophages in DFUs. ON101, the newest clinically approved product in this setting, is designed specifically to down-regulate M1 macrophages and further modulate the wound microenvironment to favour M2 emergence and expansion. Finally, the recent evolution of macrophage modulation therapies and techniques will improve the effectiveness of the treatment of diverse DFUs.